Regulação da população do afídeo Rhopalosiphum padi por predadores e parasitoides em cereais no norte do Rio Grande do Sul : abordagem por meio de modelo baseado em agente - D’Agostini, Monique (2021)
Among the species of aphids that occur in cereal crops, mainly wheat, currently, Rhopalosiphum padi (Hemiptera: Aphididae), stands out as one of the most important due to the damage it causes, especially due to the transmission capacity of barley yellow dwarf virus (BYDV). In cropping systems, the population density of pests in addition to abiotic factors is influenced by natural enemies. Simulation models based on agents are an important tool in the face of the need to monitor aphids for assertive decision-making in relation to their control. Thus, this work aimed to evaluate the role of natural enemies on the population growth of the aphid R. padi along the development of wheat, corn and black oat crops. Specifically, the objective was to: a) evaluate how the action of natural enemies fluctuates throughout the year; b) determine which natural enemies are primarily responsible for regulating the aphid population and c) establish mortality rates by natural enemies in the ABISM simulation model. The work was conducted in the experimental field of Embrapa Trigo (28 ° 13'43.4 "S, 52 ° 24 '04.7" W) between August 2019 and July 2020. Trays containing wheat plants were infested with pre-reproductive adults from R. padi and exposed to the field, monthly, throughout the cycle of wheat, corn and black oat crops. To distinguish the effect of parasitoids and predators, the trays were covered with cages that generated an exclusion effect (prevented the entry of parasitoids and predators), restriction (prevented the entry of predators) and without cage (allowing entry of parasitoids and predators). Simulations of aphid population growth, adjusting mortality rates from parasitism and predation, were performed using the ABISM model (http://200.132.58.15:6538/ABISM/). Over the course of a year, the average reduction exerted by parasitoids in the aphid population was 98.1% and by parasitoids and predators, 99.3%. The smallest population reduction was observed for the restriction system in the months of March and April and for the open system in the month of May. The biological control agents associated with aphids were coccinellids (Harmonia axyridis, Hippodamia convergens and Eriopis connexa observed in greater quantity throughout the monitoring period), sirphids (Toxomerus duplicatus and Allograpta exotica) and parasitoids (Aphidius platensis, Aphidius uzbekistanicus predominant from August to November and between April and July and Lysiphlebus testaceipes during the months of December to March). A good fit of the model between the observed and simulated data was achieved by adding variable mortality rates for each of the 12 months evaluated. The action of natural enemies is decisive in the regulation of the aphid population and its regulatory effect must be considered in the integrated management of these pests. The ABISM simulation model is an adequate tool to simulate the population growth of aphids.